VD_FINDINFO Arrêt / 2025 / 53 vom 6. Februar 2025 - VD Tribunal cantonal (2025)
LIEN DE CAUSALITÉ, ATTEINTE À LA SANTÉ PHYSIQUE, ACCIDENT | 36 al. 1 LAA, 6 al. 1 LAA, 4 LPGA, 53 al. 1 LPGA, 53 al. 2 LPGA